2009
DOI: 10.1083/jcb.200906083
|View full text |Cite
|
Sign up to set email alerts
|

Inducible proteolytic inactivation of OPA1 mediated by the OMA1 protease in mammalian cells

Abstract: A proteolytic cascade ensures that OMA1 cleaves and inactivates mitochondrial fusion protein OPA1 in times of stress, preventing damaged mitochondria from fusing with healthy organelles. (See also companion paper from Ehses et al. in this issue.)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
483
2
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 447 publications
(517 citation statements)
references
References 19 publications
22
483
2
1
Order By: Relevance
“…OPA1 was silenced only partially (to~60%) to observe mild phenotypes, as stronger OPA1 knockdown would itself induce mitophagy and apoptosis, independent of CCCP. [25][26][27] The data confirm that expression of w/t NDPK-D increases CCCP-induced CL externalization. This increase occurred under both conditions, control and OPA1 silenced, but was more statistically significant (Po0.01 versus 0.05) in OPA1-silenced cells.…”
Section: Resultssupporting
confidence: 69%
See 1 more Smart Citation
“…OPA1 was silenced only partially (to~60%) to observe mild phenotypes, as stronger OPA1 knockdown would itself induce mitophagy and apoptosis, independent of CCCP. [25][26][27] The data confirm that expression of w/t NDPK-D increases CCCP-induced CL externalization. This increase occurred under both conditions, control and OPA1 silenced, but was more statistically significant (Po0.01 versus 0.05) in OPA1-silenced cells.…”
Section: Resultssupporting
confidence: 69%
“…OPA1, beyond its classical role in inner membrane fusion, 41,42 is also directly implicated in mitochondrial quality control via its stressregulated proteolytic cleavage via OMA1. 25,26,43 In functional mitochondria, OPA1/NDPK-D interaction helps to fuel OPA1 with GTP, 44 but this topology has to be different from the one where NDPK-D is cross-linking the two mitochondrial membranes, which is kinase inactive. 7 Thus, OPA1/NDPK-D complex formation may have a role in determining NDPK-D function, and two pieces of evidence in HeLa cells support this idea.…”
Section: Discussionmentioning
confidence: 99%
“…The autophagosome fuses with the lysosome forming an autolysosome in which the mitochondrial cargo is degraded with the mitochondrial reticulum, the depolarized daughter mitochondrion is unlikely to undergo fusion and is often degraded through mitophagy. Depolarization causes the loss of Opa1 54 and Mitofusins (Mfn1 and 2), [55][56][57] proteins necessary for the fusion of the inner and outer membranes of mitochondria, and thereby promotes mitochondrial fragmentation. In agreement with the essential role of fission in mitophagy, a yeast genetic screen revealed that Dnm1, the yeast homolog of Drp1, is essential for mitophagy.…”
Section: Modulation Of Mitochondrial Dynamics Before the Onset Of Mitmentioning
confidence: 99%
“…Oma1 is evolutionarily conserved and is also found in higher eukaryotes, although a role in turnover/processing of misfolded proteins substrates has not yet been assigned. Instead, mammalian OMA1 has been shown to be the protease responsible for induced cleavage of OPA1 and will be discussed in more detail later (Ehses et al 2009;Head et al 2009). Atp23 represents yet another conserved peptidase in the IM that may contribute to the maintenance of protein quality control.…”
Section: Mitochondrial Quality Controlmentioning
confidence: 99%